Real-time Moving Object Tracking System Using Cam-shift Algorithm - Wei Song (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A real-time tracking system with the ability of tracking the moving target using cam-shift algorithm is designed. The basic technique of the stereo vision system is discussed. The architecture, the hardware component and the interface of the tracking system is analyzed. Two digital cameras are fit on the cradle head, and the electric pan/tilt/zoom controller has two independent degrees of freedom: horizontal rotation and pitch. The video signals are captured by two digital cameras, and then the position of the target is calculated. The electric pan/tilt/zoom controller is moved in order to make the target always in the surveillance window. This active system extends vision coverage over wide areas to get more detail information.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3505